War tragedy through the child perception in the modern Ukrainian prose for children and youth (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article reveals the problem of displaying military events through the prism of child perception in modern Ukrainian prose works intended for children and teens reading. Author's narrative strategies and features of autobiography as techniques of artistic writing comparative in the story by V. Rutkivsky's «Poterchata» and in the novel by S. Zhadan «Internat». It is substantiated that, in spite of the depiction of military events from different time planes, modern Ukrainian prose tends to express the idea of war as a tragedy for a child, an adult and whole humanity, and a vitality view of the future.
Keywords: military topics; modern prose; narrative strategy; autobiography